Reallocating water: An application of sequential sharing rules to Cyprus - Erik Ansink; Carmen Marchiori (Fondazione Eni Enrico Mattei (FEEM), 2009)
We present an axiomatic approach to the reallocation of water rights among economic sectors. Reallocation may be appropriate when the current schedule of water allocation is considered unfair. Our proposed approach is based on the combination of initial water rights, sectors' claims to water, and an exogenous ordering of these sectors. We apply sharing rules, based on bankruptcy rules, to reallocate water, which complements other approaches to the reallocation of water rights, including those based on water markets. Our approach is illustrated using an application to water reallocation in Cyprus, where reallocation of water rights has been recognised as an essential step towards good water governance and one of the main challenges for current water policies.
Keywords: D63; D71; Q25; 330; Water Reallocation; Sequential Sharing Rule; Water Scarcity; Axiomatic Approach; Cyprus